2009
DOI: 10.1038/ijo.2008.269
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture for obesity: a systematic review and meta-analysis

Abstract: Background and Objective: Acupuncture is widely used in complementary and alternative medicine to reduce body weight. However, a systematic review and meta-analysis to assess an effect of acupuncture has not yet been performed. Aim of this study is to critically assess evidence for reduction of body weight and to evaluate adverse events of acupuncture therapy based on the results of randomized controlled trials (RCTs) that evaluate the effect of various types of acupuncture therapies. Data sources: A total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
133
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(147 citation statements)
references
References 32 publications
4
133
0
3
Order By: Relevance
“…10 The ST36 of each leg was treated on alternate days. As the left ST36 is selected on the¯rst day of treatment, the right ST36 will be selected on the second day, then the left on the third day, and so on.…”
Section: Animal Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…10 The ST36 of each leg was treated on alternate days. As the left ST36 is selected on the¯rst day of treatment, the right ST36 will be selected on the second day, then the left on the third day, and so on.…”
Section: Animal Experimentsmentioning
confidence: 99%
“…3 Furthermore, laser acupuncture has been developed to stimulate acupuncture points on the outer skin without infection or pain, 4 and used to improve the treatment of brain function, [5][6][7] dental disease, 8,9 and obesity. 10 The laser stimulation is an alternative method for children with needle phobia. The combination of laser stimulation of CV 24 and acupressure of PC 6 is more e®ective than the laser stimulation of CV 24 alone.…”
Section: Introductionmentioning
confidence: 99%
“…The positive results may appear more with mild degrees of obesity [2]. For acupuncture as an example, a meta-analysis published in 2009 [16] investigated the randomized controlled trials (RCTs) for acupuncture compared either with placebo-controlled or with dietary intervention for obesity management and revealed that acupuncture is an efective modality for obesity treatment. However, the amount of evidence is not highly convincing because of the poor methodological quality of trials reviewed.…”
Section: Other Disciplinesmentioning
confidence: 99%
“…Among the controlled trials with positive results, the interpretation of these results is limited by such methodological problems as short duration, inadequate placebo controls, and nonstandard treatment protocols. A recently conducted systematic review and metaanalysis of acupuncture for obesity by Lee et al (2009) However, most studies have been of short duration, varying from 4 to 12 weeks. Noting that obesity is a chronic condition, it is likely to require longer periods of acupuncture treatment.…”
Section: Reflection About Acupuncture Weight Loss Research Approachmentioning
confidence: 99%